Evaluasi Pengukuran Kinerja Pemerintah Desa Dengan Menggunakan Konsep Value For Money: Studi Kasus pada Kantor Desa Tembokrejo Kecamatan Gumukmas Kabupaten Jember - Yolandha Aisyah Hadaryen; Endro Sugiartono (Jurnal Akuntansi Terapan dan Bisnis, 2021)
This study aims to measure and analyze the financial performance of the Tembokrejo Village Office, Gumukmas District, Jember Regency in 2017 to 2020 using the value for money method. Value for money is a concept of managing public sector organizations based on three main elements, namely economy, efficiency, and effectiveness. This research design uses a qualitative descriptive that describes or factual painting of facts and actual conditions on the performance of the village government. In this study, the population and sample taken were the Village Revenue and Expenditure Budget 2017–2020. The sampling technique used the census method. Data obtained by means of observation, documentation, and literature study. The results showed that the financial performance of the Tembokrejo Village Office, Gumukmas District, Jember Regency 2017–2020 in the 2017 economic measurement was not economical, 2018 was economically balanced, 2019 was not economical, and 2020 was economical. In the 2017–2020 efficiency measurement, it is stated that the efficiency is balanced every year. In measuring the effectiveness of 2017 effective, 2018 effectively balanced, 2019 effective, and 2020 effective.